Economic stratification: The remedy and demise of humanity - Cristian Călin Merce; Emilian Merce; Mihaela Mihai (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The paper shows that the world economic stratification, as well as that of all natural, social and political systems is a natural law and a prerequisite for progress. Stratification itself may mean, however, both the remedy, but also the demise of systems, by exacerbating social inequalities. The database includes the evolution of gross domestic product per capita for different time frames at European level and worldwide. The main methods employed in processing database are the indices method and expectation values of position (quartile values) used to assess the structure of Europe and world countries according to the size of the gross domestic product. In Europe, for a century, stratification has increased visibly. If in 1913, the richest country in Europe achieved a GDP per capita of 3.94 times higher compared to the poorest country, in 2013 the ratio is 13.82 to one. The status of key statistical indicators that characterize the polarization of the world by size of gross domestic product, demonstrates that stratification is less pronounced inside continents, becoming however severe, worldwide. In this regard, it is alarming that in 1994, 75% of world countries were making only 7% of the GDP per capita in the richest country (Monaco). Given that information has now become increasingly more fluid, one can include among beneficiaries, the least developed countries. Circulation of information is, however, under the command of polarizing forces, belonging to the same great powers of the world. In this way, by means of more refined methods, the benefits of progress preserve world hierarchies.
Keywords: 330; economic stratification; extreme wealth; extreme poverty